Gastroesophageal reflux disease and the functional diseases of gastro-intestinal tract: are there any interrelations? - A. A. Sheptulin; M. A. Vize-Khripunova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss possible relation of gastroesophageal reflux disease (GERD) and other functional diseases of gastro-intestinal tract (GIT) and demonstrate, which forms of GERD can be taken into account from the standpoints of functional diseases.Received data. It is shown, that the GERD is frequently combined with functional dyspepsia and irritable bowel syndrome. It can be caused by common pathophysiological mechanisms of these diseases. Within the framework of non-erosive form of GERD it is possible to define 2 subgroups of patients, at which: 1)correlation of clinical symptoms to episodes of physiological gastroesophageal reflux (GER) is present – patients with hypersensitive esophagus or 2) clinical symptoms are not related to GER at all – patients with functional heartburn, which can be considered within the framework of functional pathology. Further studies are necessary to improve diagnostics and treatment of these forms of GERD.Conclusion. Within the framework of GERD there are forms of disease which can be assessed from positions of functional disorders of GIT.